Exploring the Impact of Fly Ash on Fauna: A Comprehensive Investigation - Shikha Shrivastava; Lekhika Shrivastava (Research Advances in Environment, Geography and Earth Science Vol. 1, 2024)
Fly ash is a powdery material produced as by-product during the coal based power generation process. It is a mixture of fine, spherical particles size ranging between 0-100 microns. Fly ash contains heavy metals, trace elements with SiO2, Al2O3, Fe2O3, CaO, MgO in its basic composition and has property of deposition as sediments. The study of animals in relation to fly ash is hardly done, as much as with other pollutants very few workers are concerned with this study. This study reviews the research already done with fly ash and animals so that advancement can be brought to the subject and after finding the lacuna in already done works we can proceed to new and untouched aspects of the study of fly ash in relation to the animal world. Like N.L. Rose and his coworkers worked on soil and fly ash deposition. Several studies have been conducted to evaluate the impact of fly ash on animals and plants. These studies report the bioaccumulation of fly ash constituents in different areas in Texas. The studies also suggest that fly ash can cause lung tissue damage in mice and affect the behavior of birds and reptilian eggs. Additionally, the effect of fly ash contamination on the growth and behavior of fish has also been studied. In this paper we have studied and discussed the previous works which are focused on fly ash and its impact on animals, not only on its body but also on vital processes such as growth and tolerance against the other environmental conditions. For this study we acquired research papers from libraries, and websites, and also personally communicated with related authorities and experts during our survey. This study is important as a connecting link to observe animal population and the workers working directly on fly ash sites, as on ash dumpings or the source stations, where they will come in contact. Thus by this study we will know the amount and type of work being done and the lacuna existing in this type of study. So that our knowledge and research work can be guided in right direction.